Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/ijms18020323
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Modality System for Both Multi-Color Ultrasound-Switchable Fluorescence and Ultrasound Imaging

Abstract: Simultaneous imaging of multiple targets (SIMT) in opaque biological tissues is an important goal for molecular imaging in the future. Multi-color fluorescence imaging in deep tissues is a promising technology to reach this goal. In this work, we developed a dual-modality imaging system by combining our recently developed ultrasound-switchable fluorescence (USF) imaging technology with the conventional ultrasound (US) B-mode imaging. This dual-modality system can simultaneously image tissue acoustic structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
(43 reference statements)
0
24
0
Order By: Relevance
“…The major components have been introduced in our previous publication. 11,12 For integrity, we will very briefly introduce the entire system and emphasize the difference between the current system and the previous ones. 11,12 Similar to the previous ones, 11,12 the current USF subsystem includes the following modules: (1) an ultrasound heating and its driving module, , and generating a reference signal (RS-2) to LIA-2; FG-2: a function generator for driving the HIFU transducer by generating a 2.5 MHz sinusoidal signal and amplified by an RFPA; FG-3: a function generator to modulate the excitation laser at a 1-kHz frequency and generate a reference signal (RS-1) for the lock-in amplifier; W: a water tank to immerse the HIFU transducer and partially immerse the sample (S); ST: a silicone tube with an inner diameter (ID) of 0.31 mm and an outer diameter (OD) of 0.64 mm; 3D-TS: the three-dimensional (3-D) translational stages; TS-CU: 3-D translational stage motorized control units; CT-1: a collimation tube to focus the excitation laser into an optical bundle (OB-1); CT-2: an optimized collimation tube to guide the collected fluorescence from the optical bundle (OB-2) to the photodetector (PMT) and best eliminate the excitation light and pass the emission light; PMT: a photomultiplier tube to detect the optical fluorescence signal; Preamp: a preamplifier to amplify and filter the signal from the PMT; Laser: a 671-nm laser to irradiate the sample (S); LIA-1: a lock-in amplifier to detect the 1-kHz optical signal; LIA-2: a second lock-in amplifier to detect the signal with the HIFU-modulation frequency; NI-DAQ: a national instrument data acquisition card; CB-1: serial communication bus to control TS-MCU; CB-2: communication bus to transfer data; RS-1: a 1-KHz reference signal for LIA-1; RS-2: a reference signal with the modulation frequency for LIA-2; T-1: a trigger signal for the NIDAQ card; T-2: a single cycle digital pulse signal to trigger the movement of the 3D-TS.…”
Section: Hardware Of the Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…The major components have been introduced in our previous publication. 11,12 For integrity, we will very briefly introduce the entire system and emphasize the difference between the current system and the previous ones. 11,12 Similar to the previous ones, 11,12 the current USF subsystem includes the following modules: (1) an ultrasound heating and its driving module, , and generating a reference signal (RS-2) to LIA-2; FG-2: a function generator for driving the HIFU transducer by generating a 2.5 MHz sinusoidal signal and amplified by an RFPA; FG-3: a function generator to modulate the excitation laser at a 1-kHz frequency and generate a reference signal (RS-1) for the lock-in amplifier; W: a water tank to immerse the HIFU transducer and partially immerse the sample (S); ST: a silicone tube with an inner diameter (ID) of 0.31 mm and an outer diameter (OD) of 0.64 mm; 3D-TS: the three-dimensional (3-D) translational stages; TS-CU: 3-D translational stage motorized control units; CT-1: a collimation tube to focus the excitation laser into an optical bundle (OB-1); CT-2: an optimized collimation tube to guide the collected fluorescence from the optical bundle (OB-2) to the photodetector (PMT) and best eliminate the excitation light and pass the emission light; PMT: a photomultiplier tube to detect the optical fluorescence signal; Preamp: a preamplifier to amplify and filter the signal from the PMT; Laser: a 671-nm laser to irradiate the sample (S); LIA-1: a lock-in amplifier to detect the 1-kHz optical signal; LIA-2: a second lock-in amplifier to detect the signal with the HIFU-modulation frequency; NI-DAQ: a national instrument data acquisition card; CB-1: serial communication bus to control TS-MCU; CB-2: communication bus to transfer data; RS-1: a 1-KHz reference signal for LIA-1; RS-2: a reference signal with the modulation frequency for LIA-2; T-1: a trigger signal for the NIDAQ card; T-2: a single cycle digital pulse signal to trigger the movement of the 3D-TS.…”
Section: Hardware Of the Systemmentioning
confidence: 99%
“…[1][2][3][4][5][6] We recently developed a new imaging method for deep-tissue high-resolution imaging, which has been termed as ultrasound-switchable fluorescence (USF). [7][8][9][10][11][12][13] It has been demonstrated that USF can simultaneously achieve high SNR (or sensitivity) and high spatial resolution in tissue with a depth of centimeters. [7][8][9][10][11][12][13] In this study, we report a new method to further improve the SNR (or sensitivity) of the USF imaging without sacrificing the spatial resolution by modulating the ultrasound exposure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations